Criteria and assumptions for numerical analysis of dams - Naylor, D. J.; Stagg, Kenneth Geoffrey; Zienkiewicz, O. C. (Olgierd Cecil); British National Committee on Large Dams; Laboratorio Nacional de Engenharia Civil (Portugal) (Swansea : Department of Civil Engineering of the University College, 1975)
Includes bibliographical references.